Risk of abnormal pregnancy outcomes after using ondansetron during pregnancy: A systematic review and meta-analysis - Cao, Xiao; Sun, Mingyao; Yang, QiuYu; Wang, Qi; Hou, Liangying; Wang, Jing; Wu, Yu; Ge, Long (Frontiers in Pharmacology, 2022)
Abstract Background Hyperemesis gravidarum (HG) is a serious pregnancy complication that affects approximately 1% of pregnancies worldwide. Objective To determine whether the use of ondansetron during pregnancy is associated with abnormal pregnancy outcomes. Search strategy PubMed, Cochrane Library, CINAHL, Embase, CNKI, CBM, WANFANG, and ClinicalTrials.gov were searched for citations published in any language from inception to December 15, 2021. Selection criteria Eligible studies included any observational study. Data collection and analysis Odds ratio (OR) and 95% confidence interval (CI) were used as indicators to examine the association between ondansetron and abnormal pregnancy outcomes. Main results Twenty articles from 1,558 citations were included. Our preliminary analysis showed that, compared with the unexposed group, the use of ondansetron during pregnancy may be associated with an increased incidence of cardiac defects (OR = 1.06, 95% CI: 1.01–1.10), neural tube defects (OR = 1.12, 95% CI: 1.05–1.18), and chest cleft (OR = 1.21, 95% CI: 1.07–1.37). Further sensitivity analysis showed no significant association between ondansetron and cardiac defects (OR=1.15,95% CI: 0.94–1.40) or neural tube defects (OR=0.87,95% CI: 0.46–1.66). When controversial studies were eliminated, the results for the chest defects disappeared. Simultaneously, we found that the use of ondansetron was associated with a reduced incidence of miscarriage (OR=0.53, 95% CI: 0.31–0.89). Ondansetron was not associated with orofacial clefts (OR=1.09,95% CI: 0.95–1.25), spinal limb defects (OR=1.14,95% CI: 0.89–1.46), urinary tract deformities (OR=1.06,95% CI: 0.97–1.15), any congenital malformations (OR=1.03,95% CI: 0.98–1.09), stillbirth (OR=0.97,95% CI: 0.83–1.15), preterm birth (OR=1.22,95% CI: 0.80–1.85), neonatal asphyxia (OR=1.05,95% CI: 0.72–1.54), or neonatal development (OR=1.18,95% CI: 0.96–1.44) in our primary analysis. Conclusion In our analysis, using ondansetron during pregnancy was not associated with abnormal pregnancy outcomes. Although our study did not find sufficient evidence of ondansetron and adverse pregnancy outcomes, future studies including the exposure period and dose of ondansetron, as well as controlling for disease status, may be useful to truly elucidate the potential risks and benefits of ondansetron.